Economics of maize, soybean and cowpea processing in the northern regions of Ghana - Akinola, Adebayo A.; Maziya-Dixon, B.B.; Ayedun, B.; Abdoulaye, Tahirou (2014)
Maize, soybean and cowpea are important staple food items in Ghana. However, there is paucity of information on the economics of the processingsector in the three northern regions of Ghana. Using survey data and applying budgetary technique, Foster-Greer-Thorbecke measures of poverty andStochastic Production Frontier Function, this paper analysed costs and returns to food processors, incidence, depth and severity of as well astechnical efficiency of the processors in the sector. The results revealed that cost of materials processed represented the highest cost (>40%) itemsin all the regions. The net benefit was highest in the northern region, followed by upper east. An average processor has a net benefit per person perday of €4.30, €4.54 and €4.33 from processing Banku, Dawadawa and Kose, respectively. On a regional basis, an average processor of foodstuff hasa net benefit of €6.32, €5.09 and €6.53 in the northern region. The figures for the upper west were lowest. Although, the results indicate positive netbenefits in the study area, cost benefit ratios are not that high (<2) in all regions. The moderate poverty line for the whole northern region was€1381.00 while the core poverty line was €920.67. The moderate poverty line for northern Ghana, upper east and upper west were €1724.80,€1503.96 and €993.55, respectively. The two significant variables (p<0.1) influencing amount of food processed were raw materials that representedthe quantity of crop used in processing and amount spent on transport in the course of getting the food crop transported to point of sales. The studysuggested the need for concerted efforts aimed at increasing awareness for improved access to credit facilities as well as better transport conditionsin order to improve quantity and quality of processed food crops as ways to enhancing general livelihood of the processors in the three regions ofGhana.